THE IMPACT OF JOB DESCRIPTIONS ON EMPLOYEE PERFORMANCE - Marto Silalahi; Hendrick Sasimtan Putra; Vivi Candra; Julyanthry; Sudung Simatupang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Job descriptions are typically created by human resources professionals, hiring managers, or supervisors and are used for various purposes. The purpose of the study was to see how the results of the effect of job descriptions on employee performance at the Office of Public Housing and Settlement Areas, Pematang Siantar City, totalling 61 employees. The validity test results show that the questionnaire items have reliable criteria, as well as the reliability test that the questionnaire has double criteria. The equation results from simple regression show the value Y = 11.289 + 0.371X, this means that the results are found that the positive direction coefficient value of the job description variable on employee performance., this means that a well-structured job description can be used as a basic tool to improve employee performance.